The interrelationship between formal and informal decentralization and its impact on sub-central governance performance: The case of Vietnam - Thuy Vu Thanh; Messaoud Zouikri; Bruno Deffains (Center for Economic Studies and ifo Institute (CESifo), 2012)
Formal and informal institutions are often viewed as complements or substitutes in empirical and theoretical works. However, no evidence of complementarities or substitutes is found in our empirical analysis of the interrelation between formal and informal decentralization across 64 provinces of Vietnam. This paper finds that the formally decentralized system of public service supply is accommodating the informal one, but informal decentralization in public order provision tends to compete with the existing ineffective formal system. This implies that the central government needs to reorganize the system of decentralizing the provision of public goods/services and public in order to make informal institutions complementary rather than rival or free-riding on formal ones.
Keywords: D73; H11; H73; H83; K00; 330; formal decentralization; informal decentralization; sub-central governance; accommodating; competing; Dezentralisierung; Informeller Sektor; Regionalverwaltung; Governance-Ansatz; Deutschland